2011
DOI: 10.1007/s00059-011-3507-7
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiography versus intracardiac electrocardiography-based optimization for cardiac resynchronization therapy

Abstract: The present data show that a sustained improvement of cardiopulmonary exercise capacity can be obtained by optimizing CRT patients on the basis of an IEGM algorithm. The comparable results for cardiopulmonary exercise parameters suggest that this new method might become an important tool for adjusting CRT programming in daily practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…17 The contribution of atrial contraction to ventricular filling enhances cardiac output, thus improving clinical symptoms, LVEF and diastolic function, and decreasing brain natriuretic peptide secretion. [18][19][20] Ventricular systole and diastole begin 20-30 ms earlier in the left ventricle than in the right, although both ventricles contract at the same time. Adjusting the VV interval can partially correct the inappropriate position of left ventricular CRT leads, by optimizing the stimulation timing sequence of the left and right ventricles (but not the overall activity sequence).…”
Section: Discussionmentioning
confidence: 99%
“…17 The contribution of atrial contraction to ventricular filling enhances cardiac output, thus improving clinical symptoms, LVEF and diastolic function, and decreasing brain natriuretic peptide secretion. [18][19][20] Ventricular systole and diastole begin 20-30 ms earlier in the left ventricle than in the right, although both ventricles contract at the same time. Adjusting the VV interval can partially correct the inappropriate position of left ventricular CRT leads, by optimizing the stimulation timing sequence of the left and right ventricles (but not the overall activity sequence).…”
Section: Discussionmentioning
confidence: 99%
“…Two main factors that determine better outcomes are the optimization of atrial-to-ventricular (AV) and ventricular-to-ventricular (VV) delay (Naqvi et al, 2006). Reviewing the literature on echocardiography versus IEGM-based optimization of CRT, we found out that programming can be performed with the IEGM-based algorithm and the results are comparable with the optimization performed with the echocardiogram (Baker et al, 2007;Giammaria et al, 2016;Hua et al, 2012;Jensen et al, 2011;Kamdar et al, 2010;Pezo Nikolić et al, 2017;Reinsch et al, 2009;Sawhney et al, 2004;Wang et al, 2013;Yan et al, 2018;Zhang et al, 2019). Usually, passive ventricular filling occurs in early and mid-diastolic phases, with the blood flowing from the atrium to the ventricle secondary to AV pressure difference.…”
Section: Discussionmentioning
confidence: 85%
“…One of the five studies reported no significant difference in the NYHA classification in both groups (Yan et al, 2018). Two studies showed IEGM‐based optimization to have a better reduction in the NYHA classification than echocardiography‐based optimization (Jensen et al, 2011; Wang et al, 2013). By contrast, two studies reported echocardiography‐based optimization to be superior to IEGM in reducing the NYHA classification (Sawhney et al, 2004; Zhang et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…While we believe this to be the first pediatric study to examine this question in children, there is support for this concept in several adult studies. These studies have compared ECHO optimization by aortic VTI versus either ECG QRS duration or intracardiac electrocardiograms and showed either equivalent or superior cardiac output with ECG techniques compared to optimization by ECHO aortic VTI. However, these studies do not necessarily extrapolate to the pediatric patient population.…”
Section: Discussionmentioning
confidence: 99%